The Influence of Service Quality and Procing Strategy on Purchase Decision at Jojomanadoadventur3 Tourism Trip Services - Toha, Jescika Shintya Magdalena; Lapian, S. L. H. Joyce; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2024)
This study investigates the impact of service quality and pricing strategy on purchase decisions among consumers utilizing Jojomanadoadventur3 tourism trip services. Employing a quantitative research method, a sample of 100 respondentswas selected through simple random sampling to ensure representativeness. Data were collected using structured questionnaires assessing service quality dimensions, pricing strategies, and purchase decision variables. Statistical analysis, including correlation and regression techniques, was conducted to evaluate the relationships between the variables. The findings reveal a significant positive relationship between service quality and purchase decisions, indicating that higher service quality leads to increased consumer satisfaction and loyalty. Additionally, pricing strategy was found to significantly influence purchase decisions, suggesting that competitive pricing enhances consumer willingness to buy. This research contributes to the understanding of consumer behavior in the tourism sector and provides valuable insights for Jojomanadoadventur3 to optimize their service offerings and pricing strategy. Keywords: service quality, pricing strategy, purchase decision